2023
DOI: 10.3390/molecules28031360
|View full text |Cite
|
Sign up to set email alerts
|

Porous Framework Materials for Bioimaging and Cancer Therapy

Abstract: Cancer remains one of the most pressing diseases in the world. Traditional treatments, including surgery, chemotherapy, and radiotherapy still show certain limitations. Recently, numerous cancer treatments have been proposed in combination with novel materials, such as photothermal therapy, chemodynamic therapy, immunotherapy, and a combination of therapeutic approaches. These new methods have shown significant advantages in reducing side effects and synergistically enhancing anti-cancer efficacy. In addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…Most MOF studies focus on the uptake of the nanoplatforms, yet there is a lack of understanding of the mechanisms of MOF breakdown and clearance within tumor cells. Hence, the metabolic routes of the MOF materials should be elucidated in more detail [ 194 ]. Furthermore, tumor heterogeneity from patient-to-patient, as well as varying TME conditions (blood flow, pH variation, and oxygenation), can be a challenge for targeted drug delivery, decreasing the therapeutic efficiency [ 195 ].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most MOF studies focus on the uptake of the nanoplatforms, yet there is a lack of understanding of the mechanisms of MOF breakdown and clearance within tumor cells. Hence, the metabolic routes of the MOF materials should be elucidated in more detail [ 194 ]. Furthermore, tumor heterogeneity from patient-to-patient, as well as varying TME conditions (blood flow, pH variation, and oxygenation), can be a challenge for targeted drug delivery, decreasing the therapeutic efficiency [ 195 ].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…In vivo toxicity is yet another important limiting factor for the clinical application of nanomaterials. Despite promising results suggesting minimal cytotoxicity and toxicity of MOFs, there are still limited in vivo toxicity studies on different MOF materials [ 191 , 194 ]. Even so, preliminary studies identified that parameters such as size, shape, functionalization, and solvent systems may influence MOFs biodistribution and toxicity, as well as the use of toxic metals in the composition, such as lead, arsenic, cadmium, and chromium, which may promote severe health issues [ 196 ].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Malignant tumors seriously endanger global public health. Due to the heterogeneity of the TME [ 1 , 2 , 3 ], the efficacy of traditional treatment is often unsatisfactory. In addition, traditional treatment has obvious side effects on patients, and the tumor is prone to relapse, which greatly increases the pain of patients [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cancer treatment, MOFs are used as imaging agents and DDS. It exhibit distinct advantages that contribute to their efficacy in cancer treatment and bioimaging (Zhao Y. et al, 2022;Jin et al, 2023). It holds the capability for application in various type of bioimaging techniques, such as single/two-photon fluorescence, up-conversion fluorescence imaging, imaging, and magnetic resonance imaging.…”
Section: Bioimagingmentioning
confidence: 99%
“…It could be together with other nanomaterials to create a particle with multiple imaging features (Zhao D. et al, 2022), also it can be used for a number of biosensing methods, such as Surface-Enhanced Raman Spectroscopy (SERS), electrochemistry, as well as fluorescence. Additionally, cancer biomarkers like proteins, nucleic acids, and metabolites can be found using MOFs (Jin et al, 2023;Munawar et al, 2023). It can be functionalized with fluorescent dyes to allow for fluorescence imaging.…”
Section: Bioimagingmentioning
confidence: 99%